2020
DOI: 10.3390/ijerph17155367
|View full text |Cite
|
Sign up to set email alerts
|

Physical Literacy, Physical Activity, and Health Indicators in School-Age Children

Abstract: It has been theorized that physical literacy is associated with physical activity and health. The purpose of this study is to investigate the associations between physical literacy and health, and if this relationship is mediated by moderate-to-vigorous physical activity (MVPA). Two hundred and twenty-two children (113 girls, 10.7 ± 1.0 years old) participated in this cross-sectional study. A physical literacy composite score was computed from measures of PLAYfun, PLAYparent, and PLAYself. Physical activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
130
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(151 citation statements)
references
References 36 publications
17
130
1
3
Order By: Relevance
“…Nystrom et al [12] noted that healthy weight children presented higher CAPL scores than their overweight peers. Moreover, Caldwell, et al [40], using the Physical Literacy Assessment for Youth (PLAY), found a negative association between the %FM and PL, health-related quality of life and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Nystrom et al [12] noted that healthy weight children presented higher CAPL scores than their overweight peers. Moreover, Caldwell, et al [40], using the Physical Literacy Assessment for Youth (PLAY), found a negative association between the %FM and PL, health-related quality of life and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrate the positive relationships between physical literacy and physical activity levels (8,9). Evidence also supported the beneficial effects of physical literacy on physical fitness (8,10). Most studies have focused on linking physical literacy with the physical domain, expecting the positive impact on approaches to promote participation in physical activities through physical literacy (3).…”
Section: Introductionmentioning
confidence: 92%
“…Although slightly varying definitions exist, it has been argued both theoretically [7,9] and empirically [10][11][12][13][14] that PL is in fact a prerequisite of PA participation, making it foundational for the development, design and evaluation of PA interventions. Studies have also shown a direct association between PL and children's health [15,16] and how other behavioral habits, such as screen time, hinder PL development [17]. However, in order to evaluate the effectiveness of interventions that target an increase in children's PL, there is a need for valid measures of PL.…”
Section: Introductionmentioning
confidence: 99%